Inhibition activity of Î±-glucosidase by infusion and ethanol extract of white tea and stevia combination - Elvi Trinoviani; Ai Kholisoh; Nisa Fitriani Ar-Rifa; Ardi Rustamsyah (Jurnal Penelitian Teh dan Kina, 2016)
Ethanol extract of white tea and its stevia liquor was observed for Î±-glukosidase inhibition. The research was divided into some steps; Â white tea and stevia combination hedonic sensory test, phytochemical identification, and Î±-glucosidase inhibition activity. The result of hedonic sensory test incline towards formula 2 which consist 75% of white tea and 25% stevia. Further, this formulation was extracted by ethanol for Î±-glucosidase inhibition activity test. Formulation 2 liquor tested for enzyme inhibition activity showed IC50 value was 36,96 Âµg/ml, better than ethanol extract and acarbose. Phytochemical identification presented that both preparations contained alkaloids, flavonoids, saponins, tannins, triterpenes/steroid, and quinones.